Steel flexure and shear yielding base-mechanism for enhanced seismic resilience of RC core wall high-rise structures. Issue 1 (February 2023) - Kent, Jordyn; Zhong, Chiyun; Christopoulos, Constantin
As a result of rapid urbanization worldwide, there is an increasing demand for high-rise buildings, creating an acute need for more resilient tall structures, especially in regions of high seismicity. One of the main challenges facing design engineers is that buildings become increasingly susceptible to higher-mode effects as they become taller. Although current design practices typically achieve life-safety and collapse-prevention during major earthquake events, there is often extensive structural and non-structural damage, in great part exacerbated by the contribution of higher-mode responses. This article proposes a novel system involving a flexure and shear yielding base-mechanism, designed to limit both the first mode and higher-mode responses of a 42-story benchmark structure. These concepts only make use of well-defined buckling restrained steel braces, which have been extensively tested over many decades now and are currently implemented widely in buildings, to achieve the desired shear and flexural base yielding mechanisms. Nonlinear three-dimensional (3D) models developed in ABAQUS were used to validate key elements while models of the benchmark structure and base-mechanism were developed in ETABS to perform Nonlinear Time-History Analyses (NLTHA) for three hazard levels to investigate the global seismic response of the proposed system. Improvements among key seismic response parameters are observed at all hazard levels. By concentrating inelastic demands in the dedicated base steel yielding braces in the proposed system, quick inspection and potential repair after a major earthquake can be achieved with reduced disruptions to the use and operation of the building above.